Functionalized Multiwalled Carbon Nanotube-Reinforced Polyimide Composite Films with Enhanced Mechanical and Thermal Properties. (14th August 2019) - Chao, Min; Li, Yanming; Wu, Guanglei; Zhou, Zhenjun; Yan, Luke
Abstract : Polyimide- (PI-) based nanocomposites containing the 4, 4 ′ -diaminodiphenyl ether- (ODA-) modified multiwalled carbon nanotube (MWCNT) filler were successfully prepared. The PI/MWCNTs-ODA composite films exhibit high thermal conductivity and excellent mechanical property. The optimal value of thermal conductivity of the PI/MWCNTs-ODA composite film is 0.4397 W/mK with 3 wt.% filler loading, increased by 221.89% in comparison with that of the pure PI film. In addition, the tensile strength of the PI/MWCNTs-ODA composite film is 141.48 MPa with 3 wt.% filler loading, increased by 20.74% in comparison with that of the pure PI film. This work develops a new strategy to achieve a good balance between the high thermal conductivity and excellent mechanical properties of polyimide composite films by using functionalized carbon nanotubes as an effective thermal conductive filler.